The effect of sanctions on the job finding rate: evidence from Denmark - Michael Svarer (Institute for the Study of Labor (IZA), 2007)
This paper investigates the effect of sanctions of unemployment insurance benefits on the exit rate from unemployment for a sample of Danish unemployed. According to the findings are that even moderate sanctions have rather large effects. For both males and females the exit rate increases by more than 50% following imposition of a sanction. The paper exploits a rather large sample to elaborate on the basic findings. It is shown that harder sanctions have a larger effect, that the effect of sanctions wear out after around 3 months and that particular groups of unemployed are more responsive to sanctions than others. Finally, the analysis suggests that men react ex ante to the risk of being sanctioned in the sense that men who face higher sanction risk leave unemployment faster.
Keywords: 330; Sanctions; unemployment hazard; Arbeitsmarktpolitik; Arbeitslosenversicherung; Beschäftigung; Flexicurity; Wirkungsanalyse; Dänemark